Exercise Training Improves Memory Performance in Older Adults: A Narrative Review of Evidence and Possible Mechanisms - Babaei, Parvin; Azari, Helya Bolouki (Frontiers in Human Neuroscience, 2022)
As human life expectancy increases, cognitive decline and memory impairment threaten independence and quality of life. Therefore, finding prevention and treatment strategies for memory impairment is an important health concern. Moreover, a better understanding of the mechanisms involved underlying memory preservation will enable the development of appropriate pharmaceuticals drugs for those who are activity limited Exercise training as a non-pharmacological tool, has been known to increase the mean lifespan by maintaining general body health and improving the cardiovascular and nervous systems function. Among different exercise training protocols, aerobic exercise has been reported to prevent the progression of memory decline, provided adequate exertion level, duration, and frequency. Mechanisms underlying exercise training effects on memory performance have not been understood yet. Convergent evidence suggest several direct and indirect mechanisms at molecular and supramolecular levels. The supramolecular level includes improvement in blood circulation, synaptic plasticity and neurogenesis which are under controls of complex molecular signaling of neurotransmitters, neurotrophic factors, exerkines, and epigenetics factors. Among these varius factors, irisin/BDNF signaling seems to be one of the important mediators of crosstalk between contracted skeletal muscles and the brain during exercise training. This review provides an affordable and effective method to improve cognitive function in old ages, particularly those who are most vulnerable to neurodegenerative disorders.